China and Asia in Global Trade Slowdown - Hong, Gee Hee (IMF Working Papers; Working Paper ;, 2016)
Asia and China made disproportionate contributions to the slowdown of global trade growth in 2015. China's import growth slowed starkly, driven by both external and domestic factors, including a rebalancing of demand. Econometric results point to weak investment and rebalancing as the main causes of the import slowdown. Spillover effects from China's rebalancing are estimated for some 60 countries using value-added trade data, and are found to be more negative on Asia and commodity exporters than others.